TCH-007 Development of a Betamethasone (Dipropionate) Topical Emulsion 0.1% (W/W) (1Mg/G) For Cutaneous T-Cell Lymphoma. (12th March 2013) - Trindade, P; Mateus, D; Gonçalves, H; Sachse, MF; Machado, P; Ribeiro, HM; Gouveia, A Melo
Abstract : Background: Cutaneous lymphomas are a heterogeneous group of lymphomas characterised by T and B clonal lymphoproliferative infiltrates that appear and remain confined to the skin without evidence of involvement of other organs/systems in the six months following diagnosis. Some subtypes of cutaneous T epidermotropic lymphomas respond favourably to topical treatment with steroids. Betamethasone dipropionate is a synthetic high-potency glucocorticoid with anti-inflammatory and immunosuppressive action used as the main topical treatment in the early stages of LNH-T–Mycosis Fungoides, or as an adjuvant treatment in advanced stages of the disease. In the Portuguese pharmaceutical market only a 0.05% (w/w) (0.5 mg/g) cream is available although for this therapeutic indication strengths in a range of 0.025%–0.1% (w/w) are required. This was already an off-label clinical use and a higher concentration was required due to insufficient response to the concentration available. Purpose: To prepare and characterise a topical 0.1% (w/w) (1 mg/g) betamethasone (dipropionate) cream and evaluate the overall response in cutaneous T-cell lymphomas. Materials and Methods: Several batches of a compounded W/O emulsion containing betamethasone 0.1% (w/w) (1 mg/g) were prepared and analysed for macroscopic characteristics, pH, rheological properties and microbiological quality (total germs, fungal, yeasts and E. coli). Patients were evaluated monthly and the overall response was recorded (CR-cutaneous lesion totally disappeared; PR-partial remission – objective response >50%<100%; Stabilized disease if cutaneous lesions were similar; No response if cutaneous lesions worsened). Results: We obtained a white, homogeneous, opaque and odourless cream with a pseudoplastic behaviour. The pH of the formulations at 22 ± 3ºC was 5 (±0.5). Microbiological control for non-sterile products revealed no growth of micro-organisms. By the end of the first month one patient (11.1%) showed partial remission, the others (88.9%) had their cutaneous disease lesions stabilised. Conclusions: The topical emulsion developed has pH values and rheological characteristics suitable for drug stability and topical skin application. Clinical data is still insufficient for any conclusions. No conflict of interest.